To solve the equation system by substitution, since the equations are expressed in terms of y, you have to equal both expressions and calculate the value of x:
![\begin{cases}y=-2x+5 \\ y=-8x+17\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/e460dwicpg4bxx2gqa3aeqtfjnud55kr29.png)
![\begin{gathered} y=y \\ -2x+5=-8x+17 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kvkenfwgh15lfm91a6s7ssjk11cxexhzsn.png)
To calculate the value of x, the first step is to pass the x-term to the left side of the equation by applying the opposite operation:
![\begin{gathered} -2x+8x+5=-8x+8x+17 \\ 6x+5=17 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x0g85iicgp62mut20xa7ps1ypo7jjxzoxo.png)
Next, pass 5 to the right side of the equation:
![\begin{gathered} 6x+5-5=17-5 \\ 6x=12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7t92fdhytysbtfchdhvcnel74fu3o0nz6g.png)
Finally, divide both sides by 6 to reach the value of x
![\begin{gathered} (6x)/(6)=(12)/(6) \\ x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jb9xvppblfn26l2n0ckejuv1vwk5ttkbpo.png)
Now that we have determined the value of x, replace it in either one of the original equations to determine the value of y:
![\begin{gathered} y=-2x+5 \\ y=-2\cdot2+5 \\ y=-4+5 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/npj1gkqmx1j9bqjq7r6wqb2cr8twrtuaa9.png)
The solution for this equation system is (2,1)